Field report industrial project: Genuine Consultancy / A’isyah Maskuri - Maskuri, A’isyah (Universiti Teknologi MARA, Terengganu, 2024)
This field report provides an overview of my experiences in the field of accounting, including the collection of financial data through the use of papers that are readily available and the review of company operations. After that, the data is utilised in the process of generating the financial statements and the taxation procedures in order to fulfil the requirements of the client and the accounting standards. During the period beginning on March 3, 2024 and ending on August 23, 2024, the fieldwork was carried out at Genuine Consultancy (M) Sdn Bhd. The fundamental purpose of this study was to acquire experience in the management of accounting for businesses of varying sizes, whether they were small or large.